Computational and Cognitive Neuroscience of Vision - Zhao, Qi.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
Despite a plethora of scientific literature devoted to vision research and the trend toward integrative research, the borders between disciplines remain a practical difficulty. To address this problem, this book provides a systematic and comprehensive overview of vision from various perspectives, ranging from neuroscience to cognition, and from computational principles to engineering developments. It is written by leading international researchers in the field, with an emphasis on linking multiple disciplines and the impact such synergy can lead to in terms of both scientific breakthroughs and technology innovations. It is aimed at active researchers and interested scientists and engineers in related fields.
Neural basis of vision -- Organization of visual pathway -- Retinal mechanisms, processes, and computation -- Perceptual organization and interpretation -- Social factors of vision -- Dynamics of visual perception -- Visual illusions -- Visual disorders -- Neural basis and theory of consciousness -- Attention and cognition: biological principles and computational models -- Object recognition: biological principles and computational models -- Overview of artificial vision -- Development of robot vision -- Retinal implants -- Diagnostic sensors for visual disorders -- Cross-modal plasticity -- Vision, action, and planning -- Applications.
Keywords: Computational intelligence; Image processing -- Digital techniques; Computer vision; Neurosciences; Bioinformatics; Artificial intelligence; Computational Intelligence; Computer Imaging, Vision, Pattern Recognition and Graphics; Neuroscience; Computational and Systems Biology; Artificial Intelligence